Założenia (nie tylko) teoretyczne profilaktyki zaburzeń głosu dziecięcego = Presupposition (not only) the theoretical prevention of voice disorders in children - Gebreselassie, Jolanta (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Voice disorders in children are a significant social problem. Treatment and therapy are long-lasting and often require the cooperation of many specialists. Meanwhile, there is a consensus that effective prevention, especially addressed to children, is the optimal way of limiting phenomena are considered unfavorable.
Keywords: profilaktyka; profilaktyka zaburzeń głosu; profilaktyka zaburzeń głosu dziecięcego; czynniki ryzyka; czynniki chroniące; prevention; prevention of voice disorders; prevention of voice disorders in children; risk factors; protective factors